HUBUNGAN PENGETAHUAN, KELELAHAN, BEBAN KERJA FISIK, POSTUR TUBUH SAAT BEKERJA, DAN SIKAP PENGGUNAAN APD DENGAN KEJADIAN KECELAKAAN KERJA (Studi Pada Aktivitas Pengangkatan Manual di Unit Pengantongan Pupuk Pelabuhan Tanjung Emas Semarang) - Yohanes Kurniawan; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Loading and unloading works at Pelabuhan Tanjung Emas Semarang is fully done by TKBM. Loading and unloading work is included as heavy work activities and has a high accident risk especially on manual loading and unloading activities. Workplace accidents can be affected by knowledge, fatigue, physical workload, workplace posture, and attitude. The purpose of this study is to analyze the relationship between the variables of knowledge, fatigue, physical workloads, workplace posture, and attitude on using PPE with work accident. The type of this research is analytic observational with cross sectional approach. Population of this research is worker in Fertilizer Bagging Unit Pelabuhan Tanjung Emas Semarang who work on first shift which amounted to 42 people using total sampling method. Data collection was done by filling out work accidents, knowledge, attitude on using PPE and fatigue questionnaire and also using SNI 7269:2009 standard for performing measurement of physical workloads and using OWAS method to measure workplace posture. Data analysis using Chi Square test. The result of hypothesis test shows that there is relationship between knowledge (p = 0,014), fatigue (p = 0,003), physical workload (p = 0,000), workplace posture (p = 0,000), and attitude on using PPE (p = 0,016) with work accidents on manual handling activity at Fertilizer Bagging Unit. Employers should provide a safety talk to improve workers knowledge on occupational safety and health in order to recognize potential hazards and risks that exist in the workplace.